2020
DOI: 10.1177/0898264320917303
|View full text |Cite
|
Sign up to set email alerts
|

Self-Perceptions of Aging and Control of Life in Late Adulthood: Between-Person and Within-Person Associations

Abstract: Objectives: This study aimed to examine the longitudinal relationship between two central concepts in aging research—self-perceptions of aging (SPA) and perceived control of life (COL). Method: The data came from three measurement points over a 9-year period in the Health and Retirement Study (HRS). A random intercepts cross-lagged panel model (RI-CLPM) was estimated. Results: The covariations between SPA and COL across 9 years were evident at both the between-person level and the within-person within-time lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Previous research has shown that the way in which individuals view their own aging affects their functional health levels (Levy et al, 2002). Having positive SPA is positively related with perceived control of life (Luo et al, 2020). COVID-19 related studies showed for example, that positive SPA can help people become more resilient during the current pandemic (Losada-Baltar et al, 2020).…”
Section: Theoretical Assumptionsmentioning
confidence: 99%
“…Previous research has shown that the way in which individuals view their own aging affects their functional health levels (Levy et al, 2002). Having positive SPA is positively related with perceived control of life (Luo et al, 2020). COVID-19 related studies showed for example, that positive SPA can help people become more resilient during the current pandemic (Losada-Baltar et al, 2020).…”
Section: Theoretical Assumptionsmentioning
confidence: 99%
“…However, there is much room for further scholarly exploration in this area. For example, a recent study found that negative SPA led to decreased control of life (a construct similar to self-efficacy), while low levels of control of life also led to increased SPA after a 4 year period (Luo et al, 2020). However, another study showing that self-efficacy mediates the relationship between SPA and physical functioning also found that SPA affects physical functioning, but physical functioning does not significantly affect SPA (Tovel et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…As one behavioral pathway, more positive views on aging are associated with better health behaviors (Levy & Myers, 2004; Zhang et al, 2020), such as more physical activity (Beyer et al, 2015; Schmidt et al, 2018). As one psychological pathway, positive views on aging might enable individuals to accumulate psychological resources (Westerhof & Wurm, 2015), such as perceived control in life (Luo et al, 2020). As one physiological pathway, age stereotypes have been found to be related with cardiovascular stress reactivity and to prospectively predict cortisol levels (Levy et al, 2000; Levy et al, 2008; Levy, Ferrucci, et al, 2016).…”
Section: Sensory Functioning and Views On Agingmentioning
confidence: 99%